THE PRACTICALITY, EFFICIENCY, POSITIVE IMPACT AND EFFECTIVENESS OF THE "MIDWIFERY MANAGER" MANAGEMENT INFORMATION SYSTEM IN IMPROVING THE QUALITY OF MIDWIFERY SERVICES AT THE MIDWIFERY'S INDEPENDENT PRACTICE PLACE BANDUNG - Sutisna, Ma’mun; Rinaldi, Andi; Wijayanegara, Hidayat; Garna, Herry; Herawati, Yanti; Nurlatifah, Teni; Cherawaty, Aneu (Lux Mensana: Journal of Scientific Health, 2024)
Introduction. Health transformation in the digital era has brought fundamental changes in health services, including midwifery. About 80% of Midwife Independent Practices in Bandung City still use manual records. The management information system for Midwife Independent Practices, named "Midwifery Manager", is one of the innovations in the health sector. This study aims to analyze the increase in practicality, efficiency, positive impact, and effectiveness of the "Midwifery Manager" Management Information System in improving the quality of midwifery services at the place of practice of independent midwives. Method. The research was quantitative, with a pre-experimental design in the form of a pre-test and post-test design. The target population in this study were all midwives who had independent practice places in the Bandung City Region, which were 300 TPMB. The sampling technique in this study used proportionate random sampling, which amounted to 40 respondents. The data analysis techniques used are normality test, Wilcoxon test, and chi-square test. Result & Analysis. The results showed an increase in practicality, efficiency, positive impact, and effectiveness of the quality of midwifery services after the use of "Midwifery Manager", respectively with a value of p 0.000; p 0.000; p 0.00; and p 0.001 (<0.05) in the independent practice of midwives. Discussion. Using the Management Information System "Midwifery Manager" increases the practicality, efficiency, positive impact, and effectiveness of midwifery service quality, and effectiveness of midwifery service quality in the independent practice of midwives in the Bandung City area.